FACTORS AFFECTING FARMER MOTIVATION IN REQUESTING DUCK FARM CREDIT: A CASE STUDY IN CIREBON, WEST JAVA, INDONESIA - Saleh, A.; Lumintang, R.W. (Journal of the Indonesian Tropical Animal Agriculture, 2012)
Objectives of study was to observe and to analyze the farmer motivation in requesting farmer credit(bank loan) for duck, based on farmer characteristics and communication behavior. Sample was chosenamong duck farmers in Kroya village, Cirebon. Characteristic factors were: age, part-timer farmer, farmsize, experience, education, and income. While the communication behavior factors werecommunicating with extension worker or credit officer, and participating in social problems. Farmermotivation to apply credit impacted by their characteristics, such as educational level, income and age.Communication behavior, such as participating in extension activities and social organization,were moreimpacted to apply credit, than farmer characteristics. Communication activities can be used to persuadefarmer to apply credit.